The institutional reality of governing the Libyan embassies abroad between theory and performance indicators: “Analysis of the reports of the Libyan Audit Bureau 2012-2022” - أبوبكر مصطفى بعيرة, أنس (Dirasat in Economics and Business, 2024)
The idea of this study was generated through the controversy currently arising within the professional and academic circles of the Libyan public administration and the community demands to examine and control the ‘negative outcomes’ that began to appear from the Libyan embassies abroad. Therefore, this study seeks to explore the indicators of the regulatory and financial performance of the Libyan embassy systems. The study employs a qualitative method based on the analysis of the ‘financial supervisory documents’ to analyze the context of ‘Embassy Governance’ within the Libyan financial system.